Tailoring the surface pore morphology of bioceramic scaffolds through colloidal processing for bone tissue engineering - Shareen S. L. Chan; Daniel E. Heath; George V. Franks (PLoS ONE, 2025)
In this study, porous bioceramic scaffolds are developed with two materials, β-tricalcium phosphate (β-TCP) and hydroxyapatite (HA), with order of 10 micron-scale surface pores and approximately 40–60% volume porosity fabricated by soft templating of oil. Suitable oil and surfactant concentrations are determined for the creation of particle-stabilized emulsions with nearly spherical pores, as well as the capillary suspensions with elongated pores. The bioceramic scaffolds surfaces are then assessed for their ability to support osteoblast adhesion and growth, for applications as scaffolds for bone regeneration. The porous scaffolds’ surfaces are compared to denser surfaces of the same material, where only submicron porosity arise from partial sintering, to interrogate the impact of surface topography on cell behavior. On the denser surfaces where no large pores are templated, β-TCP supports a larger number of osteoblasts compared to HA. Templated surface porosity significantly impacts the morphology and growth of the osteoblasts. Amongst the pore morphologies, the capillary suspension demonstrates enhanced biological function, whereas the emulsion performs the poorest. The β-TCP capillary suspension scaffold surface appears to provide the most favorable conditions for the osteoblasts.